Oviduct anatomy and histology: A comparative study in four adult female Iraqi birds (review article) - Omar Altaey; Ali Hasan; Ghada Sultan; Adnan Alhasso (Basrah Journal of Veterinary Research)
The anatomy and histology of the oviduct among different birds’ species is vitally ascribed to its functional role in eggs production, eggs quality, and fertilization. Therefore, understanding the morphological parameters of the adult female oviduct facilitates the accurate diagnosis of many diseases and prevents mortalities and production losses, the current article aims to review the morphological differences of the oviduct in four local domesticated birds: (Chickens) Gallus gallus domesticus, (Ducks) Ansa ansa domesticus, (Geese) Anser anser and (Turkey) Meleagris gallopavo. The results showed that the shape, length, width and weight of the oviduct varied among different bird species. Moreover, there were significant differences in the anatomical and histological measurements of the oviduct, such as the length of mucosal folds, the thickness of oviduct wall tunics and the distribution of glands. These differences were attributed to the relationship between the oviduct and egg weight, egg shape, fertility, and the size of pelvic bones. This review has effectively summarized the similarities and differences in oviduct morphological and histological parameters. providing valuable information on species reproductive traits and potential reproductive challenges.